Dactylobasis gen. nov. from colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae) - Pérez-Gutiérrez, León Andrés (Zootaxa, 2019)
A new monobasic genus Dactylobasis is erected for D. demarmelsi sp. nov. (Holotype male, COLOMBIA, Chocó Department, Salero 05°19’01” N 76°36’52” W, alt. 129m, 10 VIII 2005. L. A. Pérez leg. UARC), is described and illustrated. The new genus is considered a member of the Teinobasini by the presence of an articulated ventral spur at the base of cercus in male. Generic characters are: mesanepisternum entirely metallic green, each with a horn in both sexes, propleuron laterally swollen with a spinulose conical posterior projection; male paraproct long with ventral branch at half of its length. Dactylobasis demarmelsi is probably endemic to the Biogeographic province of Chocó.